2019
DOI: 10.1021/acsnano.9b01180
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Reversible Control between Sliding and Pinning for Diverse Liquids under Ultra-Low Voltage

Abstract: Thermally responsive paraffin-infused slippery surfaces have demonstrated intriguing performance in manipulating the behaviors of versatile droplets. However, present methods have been limited to ex situ rigid heat sources with a high voltage of 220 V or certain specific photothermal materials, which greatly hinders its practical applications. To solve this problem, an intelligent droplet motion control actuator (DMCA) composed of paraffin wax, hydrophobic micropillar-arrayed ZnO film, and a flexible transpare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 64 publications
0
74
1
Order By: Relevance
“…By tilting the LIS, the droplet can slide along the fluid pathway [41]. This technique was improved by integrating a flexible silver nanowire heater with the paraffin-infused micropillar-arrayed zinc oxide LIS [38]. By loading a 12 V voltage on the nanowires, the paraffin becomes melting, with the interface transition from an air-liquid-liquid to a lubricated air-liquid-solid one within 40 s.…”
Section: By Varying Slipperinessmentioning
confidence: 99%
See 1 more Smart Citation
“…By tilting the LIS, the droplet can slide along the fluid pathway [41]. This technique was improved by integrating a flexible silver nanowire heater with the paraffin-infused micropillar-arrayed zinc oxide LIS [38]. By loading a 12 V voltage on the nanowires, the paraffin becomes melting, with the interface transition from an air-liquid-liquid to a lubricated air-liquid-solid one within 40 s.…”
Section: By Varying Slipperinessmentioning
confidence: 99%
“…Targeting this active direction, Yang et al summarized developments of wettability-tunable LISs induced by external stimuli and their applications in fog collection, oil-water separation, complex-flow distribution, droplets' delivery in 2019 [37]. However, with the fast advancement of smart LISs, many important and successive works on improvements of responsive LISs and other nonconventional LISs were developed for droplet manipulation [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], but these studies are not reported by Yang' work. This review is an overview of the recent progress in smart LIS for droplet manipulation induced by external stimuli, as presented in Figure 1. We first give a summary of some unique properties and fundamentals of droplets on LIS.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made to switch between the two states, mainly by manipulating the surface topology using an electrical or magnetic field 120,121. Only two recent publications highlight the use of stretchable surfaces, which show remarkable interactions with water and can be considered as mechanoresponsive materials.…”
Section: Aqueous Stimuli‐responsive Materialsmentioning
confidence: 99%
“…Slippery liquid-infused porous surface (SLIPS), as an emerging surface inspired by Nepenthes pitcher plant, has attracted widespread interest in diverse application fields such as self-cleaning, [1][2][3][4] liquid manipulation, [5][6][7][8][9] anti-biofouling, [10][11][12] anti-icing, [13][14][15] anti-corrosion, [16][17][18][19] and so on. SLIPS refers to a dynamic surface composed of a macro-or nano-structured porous substrate infused with a lubricant fluid, normally immiscible with water.…”
Section: Introductionmentioning
confidence: 99%